Konstruksi Spiritualitas Hindu Dalam Lontar Eka Prathama: Simbol, Ritual, dan Relevansi Etis-Spiritual - Luh Sri Drupadi; I Made Suweta; I Nyoman Suka Ardiyasa (Kamaya: Jurnal Ilmu Agama, 2026)
This research examines Lontar Eka Prathama as a Balinese Hindu religious text that constructs spirituality through the integrated relation among human beings, nature, and God. The study responds to the tendency to read lontar-based ritual knowledge mainly as technical instructions for ceremony, while its theological, ethical, and spiritual meanings are often left implicit. The objective is to explain the structure of human-nature-God relations, analyze the construction of spiritual knowledge through symbols and rituals, and interpret the ethical-spiritual relevance of the text for Hindu life in the era of globalization. This research uses a descriptive qualitative design with textual study and hermeneutic approach. Primary data are taken from the Indonesian translation of Lontar Eka Prathama, while secondary data are obtained from scholarly works on Hindu theology, symbolism, ritual, and hermeneutics. Data were collected through close reading, textual documentation, classification of key passages, and thematic coding. The analysis was conducted through structural-symbolic interpretation, hermeneutic distanciation, appropriation, and synthesis. The findings show that Lontar Eka Prathama places human life within a sacred process guided by Sanghyang Jagatnāta, integrates natural elements into ritual order, and constructs spiritual knowledge through tirtha, panglukatan, banten, mantra, and life-cycle rites. The text also offers ethical discipline, moral self-control, ecological awareness, and spiritual resilience by linking ritual accuracy with inner purification and cosmic responsibility. The article concludes that Lontar Eka Prathama remains relevant as a constructive source of Balinese Hindu wisdom for contemporary religious life.